Manajemen Media Digital Desa Wisata Taraju: (Studi Etnografi Virtual Tentang Manajemen Media Digital Desa Wisata Taraju) - Rachmaniar Rachmaniar; Renata Anisa (CV. Ulil Albab Corp, 2024)
Taraju Tourism Village, located in Tasikmalaya Regency, was named first place winner of the 2023 Indonesian Tourism Village Award (ADWI) in the Digital and Creative category because of its ability to accelerate digital transformation and produce creative content to promote tourism. Based on this, the author is interested in examining the digital media used by the Taraju Tourism Village using the virtual ethnographic research tradition and linking it to the concept of digital media management. The research results show that 1) Taraju Tourism Village has carried out digital media management by making good arrangements for every digital media presented; 2) Taraju Tourism Village utilizes Instagram, WhatsApp, Email, Facebook, Tiktok, Google Drive, YouTube and Website as a means of information and communication with internet users; 3) Instagram, Facebook, Tiktok and YouTube are used to provide information regarding tourism potential in the Taraju Tourism Village; 4) WhatsApp is used as a contact person for tourists who want to ask questions regarding the Taraju Tourism Village; 5) Email is used to send criticism, suggestions, messages and impressions regarding the Taraju Tourism Village; 6) Google Drive is used for tourists who want to see tour packages at Taraju Tourism Village; and 7) The website is used for tourists who will make reservations for tour packages offered at Taraju Tourism Village.